Eksistensi perempuan dalam budaya patriarki pada masyarakat muslim - Harahap, Nurhabibah; Jailani, Muhammad (Education and Social Sciences Review, 2024)
This research explores the existence of women who work in the context of patriarchal culture in Padang Baruas Village, North Sumatra. Research findings show that patriarchal culture is still strong in this village and limits women's movement in various aspects of life, including work. Women who work in this village often experience discrimination, harassment and the double burden of having to work outside the home and take care of the household. However, despite this, more and more women in this village are starting to dare to fight patriarchal culture and fight for their rights. They show that women can be successful and independent workers without having to neglect their domestic responsibilities. The aim of this research is to reveal the existence of women in patriarchal culture in the Muslim community in Padang Baruas village. The type of research used is field research using a qualitative approach which aims to understand the existence of women in patriarchal culture. Informants were determined using purposive sampling, based on the characteristics of informants who had been determined, namely working and non-working Muslim women and religious figures who lived in Padang Baruas village, data collection techniques namely observation and interviews. The data analysis technique goes through various stages, namely, data reduction, data presentation, and drawing conclusions, while the data validity technique uses triangulation of source, time, and technique. This research also found that women working in this village have various  adaptive strategies to overcome the challenges they face, such as building support networks with fellow women, challenging gender stereotypes, and fighting for their rights. The findings of this research have important implications for efforts to empower women in rural Indonesia. Comprehensive and sustained efforts are needed from various parties, including government, non-governmental organizations, and civil society, to help women in these villages reach their full potential and contribute more actively to village and community development.